Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi Dan Pengendalian Intern Terhadap Keandalan Laporan Keuangan - David Prasetyo; Mulyanto Nugroho (Jurnal Kendali Akuntansi, 2024)
The study aimed to assess how the utilization of information technology, internal control, and HR competencies affect the reliability of financial statements. Through the use of questionnaires, a "5-point Likert scale" model was used to measure the research variables. The research approach in this case is a quantitative approach,, with the population consisting of accounting and finance employees of distributor companies registered as clients of CV. BRK. Sampling is conducted comprehensively using the total sampling method, with 41 respondents serving as the research subjects. The questionnaire as an instrument that collects respondents' answers is the source of primary data. Multiple linear regression was used for data analysis, and the data was processed with the help of SPSS software version 26. The findings show that the three variables contribute to improving the reliability of financial statements significantly and also positively. This finding shows that the good implementation of internal control, the effective use of information technology, and the high competence of human resources can potentially make the reliability of financial statements increase.